Muscle strength and hormonal levels in adolescents: Gender related differences - Ramos, E.; Frontera, W. R.; Llopart, A.; Feliciano, D. (International Journal of Sports Medicine, 1998)
Zielstellung: Untersuchung der Beziehung von Muskelkraft und Serumspiegel von Testosteron (T) und Wachstumshormon GH) bei Jugendlichen beiderlei Geschlechts.